Proprioceptive Training for Knee Osteoarthritis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wang, Yi; Wu, Zugui; Chen, Zehua; Ye, Xiangling; Chen, Guoqian; Yang, Jiaman; Zhang, Peiming; Xie, Fang; Guan, Yingxin; Wu, Jiatao; Chen, Weijian; Ye, Zixuan; et al. (Frontiers in Medicine, 2021)
Background: There is increased interest in proprioceptive training for knee osteoarthritis (KOA). However, little consensus supports the effectiveness of this intervention. Objective: This meta-analysis aimed to assess the effects of proprioceptive training on symptoms, function, and proprioception in people with KOA. Methods: The PubMed, Cochrane Library, Web of Science, and EMBASE databases were systematically searched from the inception dates to April 16, 2021 for relevant randomized controlled trials (RCTs). Data were pooled by calculating the standardized mean differences (SMDs) and 95% confidence intervals (CIs). A random-effects model was used for the analyses. Results: A total of 24 RCTs involving 1275 participants were included in our analysis. This study indicated that compared to no intervention, proprioceptive training significantly improved pain, stiffness, physical function, JPS, muscle strength, mobility, and knee ROM (P＜0.05) in people with KOA. When compared to other non-proprioceptive training, proprioceptive training provided better results in terms of JPS (SMD=-1.28, 95%CI: [-1.64, -0.92], I2=0%, P＜0.00001) and mobility (timed walk over spongy surface) (SMD=-0.76, 95%CI: [-1.33, -0.18], I2=64%, P=0.01), and other results are similar. When proprioceptive training plus other non-proprioceptive training compared to other non-proprioceptive training, the two groups showed similar outcomes, but there was a greater improvement for JPS (SMD=-1.54, 95%CI: [-2.74, -0.34], I2=79%, P=0.01), physical function (SMD=-0.34, 95%CI: [-0.56, -0.12], I2=0%, P=0.003), and knee ROM (P＜0.05) in the proprioceptive training plus other non-proprioceptive training group. When proprioceptive training plus conventional physiotherapy compared against conventional physiotherapy, the two groups demonstrated similar outcomes, but there was a significant improvement for JPS (SMD=-0.95, 95%CI: [-1.73, -0.18], I2=78%, P=0.02) in the proprioceptive training plus conventional physiotherapy group. Conclusions: Proprioceptive training is safe and effective in treating KOA. There is some evidence that proprioceptive training combined with general non-proprioceptive training or conventional physiotherapy appears to be more effective and should be considered as part of the rehabilitation program. However, given that the majority of current studies investigated the short-term effect of these proprioceptive training program, more large-scale and well-designed studies with long-term follow up are needed to determine the long-term effects of these proprioceptive training regimes in KOA.